Assessment of fungal diversity and impacts of aflatoxin B1 on physiology of maize seeds (Zea mays L.) - Rani, Lucky; Sultania, Diksha; Salahuddin, Khwaja; Prasad , Gajendra (Journal of Postharvest Technology, 2023)
Maize seeds samples were collected from three locations of Darbhanga viz. Kusheshwar Asthan, Sakri and Jale with respect to mycoflora, toxin production and maize seedling growths. The number of mycoflora Aspergillus flavus, Fusarium spp, A. niger, Penicillium spp. was recorded from all the locations maize seeds. However, among all the mycoflora, A. flavus was found to be dominant. Basically aflatoxin B1, B1B2, B1B2G2 were also produced by A. flavus in SMKY Liquid media, ranging between 0.2 and 2.7 µg/l. The impact of B1 on seed germination and seedling growth was also recorded. The maximum inhibition in seed germination were observed at 2000 ppm by variety A (75.26%) and variety B (76.66%) respectively. The maximum inhibition in root and shoot lengths was also noticed in variety A (79.49%, 68%) and Variety B (71.07%, 59.71%) at 2ppm of aflatoxin B1, respectively over all my observation conclusive that the healthy seeds is the foundation of healthy plant a necessary condition for high yields.